Study and analysis of vaccination and immunization in Brazil today (Research, Society and Development, 2020)
According to the World Health Organization, researchers estimate that the spread of vaccines has allowed worldwide life expectancy to increase by 30 years in the past two centuries. Despite these advances, there are major challenges to be overcome to expand immunization coverage. Currently, the Unified Health System (SUS) offers a total of 19 vaccines that protect against more than 40 diseases free of charge. Therefore, the objective of the study was to study and analyze the current state of Brazilian vaccination in relation to infectious diseases eradicated in the country. For the development of the work, data from the Ministry of Health, published scientific articles in the Google academic, SCIELO and PubMed databases, epidemiological bulletins, as well as relevant studies and reports published on websites and internet portals through the descriptors, vaccination in Brazil, vaccination delay in Brazil, vaccines available in the single system were used (SUS). Through this work, it is concluded that the lack of information in a set of other factors generates the non-vaccination of the population, resulting in the return of previously eradicated diseases.